Gestão de custos: práticas utilizadas em propriedades rurais familiares - Gura, Andréia (2018)
The small family farmer plays a very important role in the country's food production, as it is responsible for bringing diversification to the consumer's table, producing in a smaller scale the food necessary for the daily diet of the population, becoming agriculture family a key sector for the economic development of several regions. Given the great importance of this segment, its strengthening is necessary and for this to occur several aspects must be taken into account, one of them being cost management. With structured cost management, it is possible to enter and stay in the market in a competitive way, in addition to obtaining relevant, concise and efficient information. In this sense, the use of cost management practices can help in obtaining information for decision making in various aspects regarding production. In view of the above, this study aims to map the use of cost management practices in family farms to assist decision-making regarding cost-volume-profit. In order to fulfill the objectives, the objective is to characterize the family farms in the Central South region of the State of Paraná, to identify the composition of family farms' expenditures, to analyze the use of cost-volume-profit practices in family farms, to verify the farmers' perception of the benefits provided through the use of costvolume- profit practices. For the accomplishment of this research were selected family farmers of a cooperative located in the city of Rio Azul - PR. Participants in the survey were farmers who were able to deliver their products to the government programs Food Acquisition Program and National School Feeding Program. The data were obtained through the application of a semi-structured questionnaire. The data were analyzed in an interpretative and descriptive way, through descriptive statistics. Preliminary results show that farmers interviewed have little schooling. Depreciation is the cost that farmers least control, maintaining no effective record of costs and expenses in general, has no track record of their costs as well as the calculations they say they carry out. The percentage of use of the practices contribution margin, break-even point and safety margin is low, being the practice with the highest percentage of use the contribution margin. Although family farmers make little use of practices, they recognize the importance of the benefits of using cost-management practices in decision-making, which demonstrates interest in improving property management, thereby facilitating the implementation of improvements.